2021
DOI: 10.1002/chem.202005421
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll‐Based Organic Heterojunction on Ti3C2Tx MXene Nanosheets for Efficient Hydrogen Production

Abstract: The Z‐scheme process is a photoinduced electron‐transfer pathway in natural oxygenic photosynthesis involving electron transport from photosystem II (PSII) to photosystem I (PSI). Inspired by the interesting Z‐scheme process, herein a photocatalytic hydrogen evolution reaction (HER) employing chlorophyll (Chl) derivatives, Chl‐1 and Chl‐2, on the surface of Ti3C2Tx MXene with two‐dimensional accordion‐like morphology, forming Chl‐1@Chl‐2@Ti3C2Tx composite, is demonstrated. Due to the frontier molecular orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Many materials such as metal nanoparticles (e.g., Pt, Co, Au, Cu), metallic oxides (e.g., NiO, Ru 2 O, IrO x ), and metal sulfides (e.g., NiS, SnS 2 , MoS 2 ) have been used as cocatalysts in photocatalytic systems. [16,82,83] In recent years, the 2D materials MXenes show huge potential to be used as cocatalysts due to their metal-like conductivity and suitable energy structures. According to the density functional theory (DFT) calculations, the Femi level of Ti 3 C 2 MXene is more positive than that of the CB of most typical semiconductors, indicating that it is possible for the photoelectrons migrating from semiconductors to the MXene.…”
Section: Promoting Charge Carrier Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many materials such as metal nanoparticles (e.g., Pt, Co, Au, Cu), metallic oxides (e.g., NiO, Ru 2 O, IrO x ), and metal sulfides (e.g., NiS, SnS 2 , MoS 2 ) have been used as cocatalysts in photocatalytic systems. [16,82,83] In recent years, the 2D materials MXenes show huge potential to be used as cocatalysts due to their metal-like conductivity and suitable energy structures. According to the density functional theory (DFT) calculations, the Femi level of Ti 3 C 2 MXene is more positive than that of the CB of most typical semiconductors, indicating that it is possible for the photoelectrons migrating from semiconductors to the MXene.…”
Section: Promoting Charge Carrier Separationmentioning
confidence: 99%
“…The functions of cocatalysts in photocatalytic system are mainly reflected in the following aspects. [15][16][17] First, introducing a cocatalyst with higher work function than that of the semiconductors can facilitate the carrier separation via a charge transfer process from semiconductor to the cocatalyst. Second, the photogenerated carriers could undergo a fast migration to the semiconductor surface in the presence of cocatalysts, resulting in the effective suppression of photocorrosion and therefore improving the stability of the catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…Among various cocatalysts, ultrathin 2D noble-metal-free transition metal carbon/nitride Mxenes (e.g., Ti 3 C 2 T x ) have received widespread attention in the eld of photocatalysis due to their wide light absorption capacity, abundant surface bridging groups and unsaturated active metal centers. [29][30][31] Moreover, the ultrathin 2D Mxenes have proven to be an ideal support to in situ construct 2D/2D heterostructured photocatalysts. [32][33][34] For instance, Huang et al reported the photocatalytic overall water splitting with ultrathin 2D/2D Ti 3 C 2 / BiVO 4 nanosheets with enhanced performance compared to pure BiVO 4 due to the improved charge transfer towards the cocatalyst Ti 3 C 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] PHE systems based on various kinds of semiconductors have been extensively investigated so far, [7,8] among which Pt/TiO 2 has been regarded as one of the most major photocatalysts. [9][10][11][12][13] To overcome the inherent defects of TiO 2 such as large band gap which leads to low photocatalytic efficiency, some research groups reported the development of dye-sensitized Pt/TiO 2 photocatalysts for hydrogen evolution. [14][15][16][17] A recent trend for sensitizing Pt/TiO 2 is the use of metal-free organic dyes with strong absorptivity and panchromatic sensitization properties.…”
mentioning
confidence: 99%